Luminance sticker based facial expression recognition using discrete wavelet transform for physically disabled persons - Nagarajan, Ramachadran, Prof. Dr.; Hariharan, Muthusamy; M., Satiyan (Springer Science+Business Media, LLC., 2012)
Link to publisher's homepage at http://www.springerlink.com/